2020
DOI: 10.21037/gs-20-378
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive iodine treatment of papillary thyroid carcinoma in Japan

Abstract: We have a unique history of using radioactive iodine (RAI) therapy and surgical treatment for thyroid cancer in Japan. Less than total thyroidectomy without RAI therapy was the most common management of papillary thyroid carcinoma (PTC) in the past. Limited availability of dedicated facilities for the RAI administration due to the strict regulations and insufficient coverage of the expenses were the major reasons that impacted on the management decisions. Following the publication of the Japanese clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We suggested that pN1b patients with total thyroidectomy should accept a subsequent RAI treatment, which completely remove tumor and residual thyroid tissue to prevent the recurrence and distant metastasis by promoting sufficient I 131 to enter the residual thyroid tissue and metastatic focus [ 36 , 37 ]. However, RAI should only be employed in patients with a total thyroidectomy because I 131 can damage normal thyroid tissue [ 13 ]. It may be necessary to evaluate NMLNs and estimate the effect of RAI treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggested that pN1b patients with total thyroidectomy should accept a subsequent RAI treatment, which completely remove tumor and residual thyroid tissue to prevent the recurrence and distant metastasis by promoting sufficient I 131 to enter the residual thyroid tissue and metastatic focus [ 36 , 37 ]. However, RAI should only be employed in patients with a total thyroidectomy because I 131 can damage normal thyroid tissue [ 13 ]. It may be necessary to evaluate NMLNs and estimate the effect of RAI treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to evaluate the clinical and prognosis significance of NMLNs ≥ 5 among pN1 patients. It was noted that there were great differences in cervical LNM of patients with PTC and the surgical treatment of LNs for patients with PTC among different hospitals is still different and depends on the judgment of surgeon on the procedural safety [ 6 , 12 , 13 , 21 ].…”
Section: Methods and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not be a standard treatment, globally, but is a common practice in many cities in Japan. High-dose RAI therapy is not performed for many patients with recurrent differentiated thyroid cancer in Japan due to the very limited number of facilities available for high-dose RAI therapy since the use of radiation is unpopular for historical reasons [ 17 , 18 ]. Furthermore, there was a report that the diagnostic RAI scintigraphy using small amounts of RAI can predict the efficacy of high-dose RAI therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 One of these is the ATA guidelines, and similar risk factors have also been proposed in Japan. 3,5 Although the risk slightly differs depending on the treatment of 1-2 cm tumors and metastatic lymph nodes, these evaluations are based on the TNM classi cation.…”
Section: Discussionmentioning
confidence: 99%